A Holistic Exploration of Quality Assurance Mechanisms at Systemic and Institutional Levels: Conceptualisation, Perception and Practices in Pakistani Higher Education Institutions - TAIYABI, FATEMA HUZEFA (2025)
This thesis explores Quality Assurance (QA) mechanisms at systemic and institutional levels in Pakistani Higher Education Institutions (HEIs), focusing particularly on stakeholder conceptualisation, perceptions, and QA practices. Grounded in frameworks such as the World Culture Theory, Neo-Institutional Theory, Stakeholder Theory, Total Quality Management (TQM), and Theory of Change (ToC), this study examines the coherence between the National Agenda and National Policies in relation to Quality Assurance (QA) in higher education. This research investigates the interplay between global QA benchmarks and local QA standards, specifically analysing how Pakistan's QA mechanisms align with the European Standards and Guidelines (ESG). Furthermore, it examines the alignment between External Quality Assurance (EQA) and Internal Quality Assurance (IQA) practices through the Precepts, Standards, and Guidelines (PSG) QA framework, evaluating its relevance to both local needs and international compatibility. Using a mixed-methods approach, data were gathered through document analysis, surveys, interviews, and focus groups, with the sample comprising representatives from the Higher Education Commission (HEC), QA practitioners, full-time faculty, and postgraduate students across eight universities in Pakistan. The study employed quantitative sampling with quality practitioners (n=80), faculty (n=158), and students (n=204) to ensure representative data. For qualitative analysis, participants included HEC members, quality practitioners, faculty, and postgraduate students, who contributed through focus groups (n=32) and open-ended questions (n=22), providing diverse insights across various disciplines and institutions. Quantitative data were analysed using SPSS, whereas qualitative data were processed using NVivo. The research identifies significant themes, including EQA and IQA practices, evaluation processes, actors involved in QA, and Continuous Improvement Processes. The findings highlight significant systemic and institutional challenges impeding the effectiveness of QA mechanisms, including insufficient training and empowerment of QA staff, as well as inadequate review processes. Furthermore, governance constraints, limited resources, and the inefficient allocation of funds hinder the successful implementation of QA frameworks. These factors often lead to regulatory compliance, rather than promoting a culture of continuous improvement. The two major contributions of this research are the development of the Quality Assurance Review Tool (QART), a comprehensive assessment instrument designed to advocate and offer practical insights into effective QA applications. In addition, the findings led to the development of a Theory of Change (ToC) action plan that offers strategic insights for policymakers and institutions to ensure and enhance QA systems in Pakistan's Higher Education Institutions, ensuring alignment with global standards, while addressing local challenges.